Comparison of the Differences between Two-Photon Excitation, Upconversion, and Conventional Photodynamic Therapy on Cancers in In Vitro and In Vivo Studies - Chuanshan Xu; Siu Kan Law; Albert Wing Nang Leung (MDPI AG, 2024)
Photodynamic therapy (PDT) is a minimally invasive treatment for several diseases. It combines light energy with a photosensitizer (PS) to destroy the targeted cells or tissues. A PS itself is a non-toxic substance, but it becomes toxic to the target cells through the activation of light at a specific wavelength. There are some limitations of PDT, although it has been used in clinical studies for a long time. Two-photon excitation (TPE) and upconversion (UC) for PDT have been recently developed. A TPE nanoparticle-based PS combines the advantages of TPE and nanotechnology that has emerged as an attractive therapeutic agent for near-infrared red (NIR) light-excited PDT, whilst UC is also used for the NIR light-triggered drug release, activation of 'caged' imaging, or therapeutic molecules during PDT process for the diagnosis, imaging, and treatment of cancers. Methods: Nine electronic databases were searched, including WanFang Data, PubMed, Science Direct, Scopus, Web of Science, Springer Link, SciFinder, and China National Knowledge Infrastructure (CNKI), without any language constraints. TPE and UCNP were evaluated to determine if they had different effects from PDT on cancers. All eligible studies were analyzed and summarized in this review. Results: TPE-PDT and UCNP-PDT have a high cell or tissue penetration ability through the excitation of NIR light to activate PS molecules. This is much better than the conventional PDT induced by visible or ultraviolet (UV) light. These studies showed a greater PDT efficacy, which was determined by enhanced generation of reactive oxygen species (ROS) and reduced cell viability, as well as inhibited abnormal cell growth for the treatment of cancers. Conclusions: Conventional PDT involves Type I and Type II reactions for the generation of ROS in the treatment of cancer cells, but there are some limitations. Recently, TPE-PDT and UCNP-PDT have been developed to overcome these problems with the help of nanotechnology in in vitro and in vivo studies.